Alcohol packaging as a promotional tool: A focus group study with young adult drinkers in Scotland. (20th October 2021) - Jones, D; Moodie, C; Purves, RI; Fitzgerald, N; Crockett, R
Abstract: Background: Given the dearth of research on consumer perceptions of alcohol packaging as a marketing tool, with existing studies focused on children and adolescents, our aim was to explore how young adults view and engage with alcohol packaging. Methods: Eight focus groups were conducted in Glasgow (Scotland) in September 2019 with young adult drinkers (n = 50), segmented by age (18-24, 25-35), gender (female, male) and social grade (ABC1, C2DE). Participants were shown, allowed to handle, and asked about, a range of alcoholic products. Data were analysed thematically using an inductive approach. Results: Five main themes emerged from the data. The first was the ubiquity of alcohol packaging, with frequent exposure reported in different settings, such as shops and drinking venues, and via marketing. The second was appeal, with pack graphics (e.g. colour), structure (e.g. shape, size) and promotions (e.g. gifts, limited-editions) allowing alcohol packs to capture attention, enable products to stand out on shelves, and help create product and brand liking, interest and choice. Third, alcohol packaging was frequently associated with specific occasions and activities. Fourth, alcohol packaging informed perceptions of product-consumer targeting, suitability, and intended drinker profiles. Fifth, alcohol packaging also engaged non-visual senses, guiding expectations of product taste and palatability. Conclusions: For young adult drinkers in Scotland, alcohol packaging can capture attention, create appeal, and help shape perceptions of the product, drinker and drinking experience. Key messages: Alcohol packaging is a key marketing communications vehicle, which can attract attention, create product and brand liking, interest and choice, guide expectations, and influence purchasing decisions. Alcohol packaging conveys messages of consumer-product suitability and acceptability, helping to reinforce perceptions that alcohol is a desirable product via pack structure, graphics, and promotions.